An unusual case of Behcet disease with posterior scleritis: A case report. Issue 35 (August 2019) - Yanagida, Chihiro; Usui, Yoshihiko; Sakai, Jun-Ichi; Goto, Hiroshi
Abstract: Rationale: Posterior scleritis is an ocular inflammatory disorder that can be associated with both infectious and non-infectious immune reactions. Behcet disease is a chronic, relapsing, multisystemic inflammatory disorder with uveitis. There are no reported cases of posterior scleritis with Bechet disease. Patient concerns: A 50-year-old man previously diagnosed with systemic Behcet disease presented with ocular pain and decreased vision in the left eye. Diagnosis: Posterior scleritis associated with Behcet disease was diagnosed based on optical coherence tomography showing choroidal folds, as well as contrast computed tomography and ultrasound sonography demonstrating thickening of the posterior sclera. Interventions: Treatment with systemic corticosteroids was initiated. Since inflammation relapsed during steroid tapering, anti-tumor necrosis factor-alpha (TNF-α) therapy was used in combination, and tapering of steroids was possible without recurrence of inflammation for 12 months. Outcomes: Posterior scleritis was resolved and visual acuity improved. With the continuation of TNF-α therapy, oral prednisolone was successfully tapered and discontinued. No relapse of inflammation was observed at follow-up 1 year after discontinuation of prednisolone. Lessons: Ophthalmologists should be aware of the possibility of rare manifestation of posterior scleritis in patients with Behcet disease, and that combined use of systemic steroids and anti-TNF-α therapy may resolve the scleritis without recurrence of inflammation.